Drudgery, Not Slavery: How and Why John Locke Stays True to Exodus 21 in “Of Slavery” - Kurtz, Yoni (Iggrot Ha'Ari, 2023)
John Locke’s philosophy of slavery has been oft-disputed; despite arguing against the persistence of slavery as an institution in his political philosophy, Locke was involved in colonial projects that legalized slavery. While many scholars have attempted to analyze this contradiction, relatively few have examined Locke’s use of biblical allusion in his seminal work on slavery, the aptly named “Of Slavery.” Though Locke’s mention of “slavery among the Jews” in this essay seems at first to be haphazard, by analyzing Locke’s textual fidelity and potential personal motivations for it one can see the lasting rhetorical and social impact of the story of Exodus on later religious groups and their own philosophical understandings of slavery. Overall, we see that despite the obvious differences in context between ancient Egypt and Locke’s seventeenth century England, Locke’s personal identification with the story of the Hebrews moved his arguments on slavery towards a more biblical understanding.